Association of serum calcium level with periodontitis: a cross-sectional study from NHANES 2009–2014 - Cao, Hongliang; Wang, Min; Duan, Mengna; Wang, Song; Zhang, Haiyang (Frontiers in Nutrition, 2025)
PurposeThis study aimed to investigate the association between serum calcium levels and periodontitis in a U.S. adult population, using data from the National Health and Nutrition Examination Survey (NHANES) 2009–2014.MethodData were analyzed from 8,601 participants aged over 30 years, who were categorized based on the presence or absence of periodontitis. Serum calcium levels were measured using standardized NHANES protocols, and periodontitis status was determined through clinical oral examinations. To assess the relationship between calcium levels and periodontitis, multivariate logistic regression models were applied across three levels of adjustment. Additionally, trend tests and subgroup analyses were conducted to explore associations across different demographic and clinical subgroups. A smoothing curve fitting and threshold effect analysis were also performed to examine potential nonlinear relationships.ResultsAfter adjusting multiple covariates, participants in the highest quartile of serum calcium showed an 18% reduced risk of periodontitis compared to those in the lowest quartile (OR = 0.82, 95% CI: 0.71–0.95, p = 0.0083; p for trend = 0.0057). The association remained stable across various subgroups. Smoothing curve fitting indicated a nonlinear negative correlation between calcium levels and periodontitis, though without a significant inflection point at 2.48 mmol/L (p = 0.094).ConclusionElevated serum calcium levels appear to be associated with a lower risk of periodontitis in adults. These findings suggest that adequate calcium intake may play a role in periodontitis prevention, providing valuable insight for clinical guidance on nutritional and preventive strategies in periodontal health.